Examining the relationship between service quality and student satisfaction in Malaysian university sports facilities through servqual assessments of service quality / Siti Khairunisa Othman and Mohamad Firdaus Ahmad - Othman, Siti Khairunisa; Ahmad, Mohamad Firdaus (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study investigates the relationship between service quality and students’ satisfaction at UiTM Seremban Campus sport facilities. Despite growing demand for improved service performance in Malaysia, universities face challenges in maintaining sports facilities due to funding limitations, affecting operational quality [1,2]. By identifying service quality levels, satisfaction levels, and their relationship, this research addresses the gap in enhancing students’ experiences and optimizing facility management [1]. A quantitative research design was employed, utilizing a survey questionnaire distributed via Google Forms. The sample consisted of 361 students from UiTM Seremban Campus, selected using Krejcie and Morgan's (1970) sampling method. This approach enabled the collection of numerical data to analyze service quality and student satisfaction levels and examine their relationship